Perancangan Tata Letak Gudang SSI 3 dengan Menggunakan Metode ABC dan Class Based Storage di PT. Sami Surya Indah Plastik - Adit Tri Wahyono; Indah Wahyu Utami; Febrina Agusti (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Warehouse SSI 3 of PT. Sami Surya Indah Plastik is a polymer raw material storage facility of approximately 1,088 m², storing main raw materials (HDPE, LLDPE), supporting materials (metalonce, pellet, calcium), and external raw materials. The existing layout suffers from misplaced raw materials, the absence of grouping based on movement frequency, and dependence on a single operator, resulting in an average waiting time of up to 30 minutes. A physical constraint also exists in the form of a maximum stacking limit of 2 pallets due to safety factors. This study analyzes the suitability of raw material placement, designs a proposed layout using ABC classification and class-based storage (CBS), and compares performance using historical data from January–December 2025. The ABC classification results formed the basis for the proposed storage zoning, evaluated through FlexSim simulation. The proposed layout reduced total material handling moment from 59,013,313.97 kg/m to 49,688,902.90 kg/m and weighted average distance from 13.38 m to 11.27 m, each with 16% efficiency.